Association between painful temporomandibular disorders and sleep quality: A systematic review. (26th May 2020) - Dreweck, Fabiana Dias Simas; Soares, Simone; Duarte, Joyce; Conti, Paulo César Rodrigues; De Luca Canto, Graziela; Luís Porporatti, André
Abstract: This review aimed to systematically evaluate the association between painful temporomandibular disorders (TMD) and sleep quality in adults. Observational case‐control studies using either RDC/TMD or DC/TMD for TMD diagnostic and validated questionnaires for sleep quality were selected by two reviewers in a two‐phase process. A systematic review was conducted in accordance with the PRISMA statement. The search was performed in PubMed/MEDLINE, LILACS, SCOPUS, PsycINFO, Web of Science and Grey literature (ProQuest, Google Scholar and OpenGrey). To be eligible, studies had to include adults (>18 years old), with no language, gender or time of publication restrictions. The quality of the papers was assessed using the Newcastle‐Ottawa Scale (NOS). Eight case‐control studies were included, with high (4) and moderate (4) quality assessment. Seven studies reported a significant association between the presence of painful TMD and sleep quality ( P < .05), while the other found impaired sleep in participants with higher sensitivity to heat pain ( P < .001). When pain levels were concerned, using different pain scales, six studies found differences when compared to control groups. One study showed that in non‐painful TMD, the PSQI values were not different when compared to the control group. An association exists between painful TMD and sleep quality. The presence of pain seems to strongly impact the sleep quality in TMD patients.